2018
DOI: 10.1108/ijse-10-2016-0292
|View full text |Cite
|
Sign up to set email alerts
|

The effect of child labour on children’s health in Brazil

Abstract: Purpose The purpose of this paper is to examine if child labour can have long-term consequences on children’s health status. Design/methodology/approach To capture this relationship, this paper uses the Brazilian National Household Survey (PNAD) conducted in 1998, 2003 and 2008, structured as a pseudo panel and estimated using a fractional response model. Findings The results show that child labour is negatively associated with child’s health status, and the longer the hours worked, the worse is the child’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…8 Ideas for future work on child labour Evidence from the literature, including studies such as Nishijima, Souza and Sarti (2015) and Nicolella and Kassouf (2018), has shown the effects of engaging in child work on health outcomes. These studies have shown that early labour market entry is associated with poor physical health in adulthood.…”
Section: Re-examining Child Labour Through a New Lensmentioning
confidence: 99%
“…8 Ideas for future work on child labour Evidence from the literature, including studies such as Nishijima, Souza and Sarti (2015) and Nicolella and Kassouf (2018), has shown the effects of engaging in child work on health outcomes. These studies have shown that early labour market entry is associated with poor physical health in adulthood.…”
Section: Re-examining Child Labour Through a New Lensmentioning
confidence: 99%
“…Ahmed and Ray [7] about the health consequences of child labor in Bangladesh. Farther research by Nicolella and Kassouf [8]on the Effects and Child Labor on Children's Health in Brazil. In addition there is also Hurst [9] on Health and Child Labor in the Agricultural Sector.…”
Section: Introductionmentioning
confidence: 99%
“…In a short-term research by O'Donnell, Rosati and Doorslaer [6]; Beegle, Dehejia and Gatti [10] discovered that there is correlation between child labor and health. Nevertheless, Nicolella and Kassouf [8] discovered the correlation between child labor and health in long-term.…”
Section: Introductionmentioning
confidence: 99%